A relação terapêutica frente a homossexualidade - Kniest, Gustavo Rihl (2005)
It is intended through this research to understand how the clinic psychologist interacts with the homosexuality brought by clients during the therapeutic process. The homosexuality, which until recently was considered as a disease or a behavioral deviation, is gaining special attention from the Psychology professionals not only because its incidence is rising among adolescents, but also because under the contemporary cultural configurations it is a phenomenon that needs to be revaluated. Taking the homosexuality historical and cultural evolution as reference - including some of its theoretical approaches - and also reviewing the authors that studied the establishment and development of Psychology as science and profession, it was possible to draw a map allowing us to come closer to the psychologist s proceeding, his/her role, his/her difficulties and contributions, and the influence of culture upon the therapist s practice. Also, taking the phenomenological method as theoretical reference, and performing individual interviews, a qualitative research was developed, aiming to unveil the experience and resonance of therapists working with clients that face homosexual issues. Reports full of reflections and contributions lead to a surprising picture: under solving/curative demands, along with psychological theories openly biased to pathological concepts, therapists relate a clinical intervention directed to a perception of man as an entire being, allowing them a critical theoretical and social attitude regarding this growing occurrence in their offices. On the other hand, therapists reveal an unassisted theoretic/professional position when dealing with this issue and with the family/social background of their clients. On calling attention to this situation we hope to contribute to the need of further reflection and also to offer a point of view that set in motion a critical thinking regarding this matter, and to find the place of the psychologist as a professional exploring this panorama